Generalized Szász-Kantorovich Type Operators - Kajla, Arun; Araci, Serkan; Goyal, Meenu; Acikgoz, Mehmet (Communications in Mathematics and Applications, 2019)
In this note, we present Kantorovich modification of the operators introduced by V. Miheşan [Creative Math. Inf. 17 (2008), 466 – 472]. First, we derive some indispensable auxiliary results in the second section. We present a quantitative Voronovskaja type theorem, local approximation theorem by means of second order modulus of continuity and weighted approximation for these operators. Furthermore, we show the rate of convergence of these operators to certain functions with the help of the illustrations using Maple algorithms.